1997
DOI: 10.1002/(sici)1099-1573(199703)11:2<147::aid-ptr41>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic Effect of Moringa stenopetala Aqueous Extract in Rabbits

Abstract: The hypoglycaemic effect of Moringa stenopetala extract was assessed in nondiabetic rabbits by blood glucose analysis. In vivo experiments were carried out in rabbits that received the test material and the standard, glibenclamide. The plant extract, although less potent than glibenclamide, was found to lower blood glucose concentration. The hypoglycaemic effect was observed to increase with time and with an increase in the dose of the extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 1 publication
(1 reference statement)
1
38
0
1
Order By: Relevance
“…The Wealth of India, 1962;Padmarao et al, 1996;Dahot, 1988;Ruckmani et al, 1998Morton, 1991Fuglie, 2001;Makonnen et al, 1997;The Wealth of India, 1962;Dahot, 1988Bhatnagar et al, 1961Siddhuraju andBecker, 2003 Fuglie, 2001 Nair and Subramanian, 1962; Bhattacharya et al, 1982;Dahot, 1998;Siddhuraju and Becker, 2003;Mehta et al, 2003Faizi et al, 1998 …”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wealth of India, 1962;Padmarao et al, 1996;Dahot, 1988;Ruckmani et al, 1998Morton, 1991Fuglie, 2001;Makonnen et al, 1997;The Wealth of India, 1962;Dahot, 1988Bhatnagar et al, 1961Siddhuraju andBecker, 2003 Fuglie, 2001 Nair and Subramanian, 1962; Bhattacharya et al, 1982;Dahot, 1998;Siddhuraju and Becker, 2003;Mehta et al, 2003Faizi et al, 1998 …”
Section: Referencesmentioning
confidence: 99%
“…The fresh leaf juice was found to inhibit the growth of microorganisms (Pseudomonas aeruginosa and Staphylococcus aureus), pathogenic to man . Makonnen et al (1997) found Moringa leaves to be a potential source for antitumor activity. O-Ethyl-…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moringa oleifera preparations have been used for its anti-trypanosomal, hypotensive, antispasmodic, antiulcer, anti-inflammatory, hypocholesterolemic, and hypoglycemic activities, as well as having considerable efficacy in water purification by flocculation, sedimentation, antibiosis and even reduction of Schistosome cercariae titer 18 .…”
Section: Fig 1: Benzyl Isothiocyanate (1) and Pterygospermin (2) Fromentioning
confidence: 99%
“…Approximately every part of M. oleifera that is, fruit, root, seed, gum, bark flowers, leaf, and seed oil have been employed for various disorders in the indigenous South Asian medicine, involving the management of inflammation and infectious diseases (Caceres et al, 1991;Anwar et al, 2007;Kumar et al, 2009;Upadhyay et al, 2015). Flowers, leaves, seed, fruit, bark, roots and immature pods work as circulatory and cardiac stimulants (Makonnen et al, 1997;Verma et al, 2012) and have antitumor, anti-inflammatory, antimicrobial, antiprogestational, antiaging, antiepileptic, antiulcer and antipyretic activity (Pal et al, 1995;Paliwal and Sharma, 2011;Ganatra et al, 2012;Koul and Chase, 2015). These different parts of tree have also been utilized for nutritional purposes as well (Ashfaq et al, 2012).…”
Section: Introductionmentioning
confidence: 99%